Cytokine gene polymorphisms in sarcoidosis - Vasakova, M.; Sterclova, M.; Kolesar, et al., L. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Background: Sarcoidosis is a disease characterized by granuloma formation in many organs, but mostly in lung and lymph nodes. The immunopathogenic background of the disease is probably based on disregulation of immune response to different antigens. The imbalance of immune reactivity might be influenced by genetic background. In our study, we have investigated cytokine genetic polymorphisms in sarcoidosis group and compared the results with that of a group of healthy volunteers. Methods: Thirty one sarcoidosis patients were enrolled to our study. Basic demographic data were collected. Polymorphisms in the promoter regions of the IL-1alpha, IL-1beta, IL-1R, IL-1RA, IL-2, IL-4, IL-6, IL-10, IL-12,TNF-alpha, IFN-gamma and in the translated regions of the TGF-beta, IL-1 beta, IL-2, IL-4 and IL-4RA genes were characterized. Results: For IL-10, the (-819) and (-592) CC homozygosity was statistically more frequent in the sarcoidosis group compared to healthy controls. According to the haplotypes, the majority of sarcoidosis patients had IL-10 (-1082)(-819)(-592) ACC haplotype 2 compared to controls with ATA in most of the cases. Conclusions: The results of our study support the hypothesis of a genetically encoded immune regulation imbalance in sarcoidosis. The high-producer IL-10 (-819) and (-592) CC genotypes and intermediate- producer IL-10 (-1082) (-819) (-592) ACC haplotype 2 present in the majority of our sarcoidosis patients could support the role of genetically encoded disregulation of cell- mediated immune response to an unknown antigen